Inovasi Leksikal Bahasa Sunda Di Kabupaten Majalengka : Kajian Geografi Dialek - Hadinata Prayoga (Bahasa Indonesia Prima, 2024)
As a nation consisting of various tribes and cultures, Indonesia has a variety of regional languages that coexist with the national language. Sundanese is a regional language with many speakers. This research describes and maps Sundanese language innovation in Majalengka which includes the geographical distribution of dialectical variations phonological, morphological and lexical in full). The study employs a qualitative approach with a descriptive presentation, starting from providing data, questionnaires, data analysis, and presenting research reports. The data used in this study is the Sundanese language spoken in Maja District. The results of the research show that in Maja District there are language variations which are divided into phonological variations, morphological variations and lexical variations. It can also be seen that several villages predominantly show internal innovation which is the identity of Maja District.